Earnings conference calls and stock returns: The incremental informativeness of textual tone - Price, S. McKay; Doran, James S.; Peterson, David R.; Bliss, Barbara A. (Journal of Banking & Finance, 2012)
Quarterly earnings conference calls are becoming a more pervasive tool for corporate disclosure. However, the extent to which the market embeds information contained in the tone (i.e. sentiment) of conference call wording is unknown. Using computer aided content analysis, we examine the incremental informativeness of quarterly earnings conference calls and the corresponding market reaction. We find that conference call linguistic tone is a significant predictor of abnormal returns and trading volume. Furthermore, conference call tone dominates earnings surprises over the 60 trading days following the call. The question and answer portion of the call has incremental explanatory power for the post-earnings-announcement drift and this significance is primarily concentrated in firms that do not pay dividends, illustrating differences in investor behavior based on the level of cash flow uncertainty. Additionally, we find that a context specific linguistic dictionary is more powerful than a more widely used general dictionary (Harvard IV-4 Psychosocial).